Comparison of commercially available, rapid, point-of-care C-reactive protein assays among children with febrile illness in southwestern Uganda. - Caitlin A Cassidy; Lydiah Kabugho; Georget Kibaba; Bradley Lin; Brandon Hollingsworth; Emmanuel Baguma; Jonathan J Juliano; Edgar M Mulogo; Ross M Boyce; Emily J Ciccone (Public Library of Science (PLoS), 2024)
In Uganda, children with febrile illness are often treated with antibiotics even though most have self-limiting, likely viral, infections. C-reactive protein (CRP) measurement can help identify those who are more likely to have a bacterial infection and therefore need antibiotic treatment. Implementation of a CRP rapid diagnostic test (RDT) at the point-of-care in resource-constrained settings with minimal laboratory infrastructure could reduce unnecessary antibiotic use. In this study, we evaluated the performance of three semi-quantitative CRP RDTs (Actim, BTNX, Duo) against a reference CRP assay requiring an electrically powered analyzer (Afinion). While both tests demonstrated substantial agreement with Afinion, Actim had slightly higher agreement than BTNX. The sensitivity was higher for the BTNX test, whereas the Actim test had a higher specificity, at cut-offs of 40 mg/L and 80 mg/L. At a cut-off of 20 mg/L, Duo demonstrated substantial agreement with the Afinion test as well. Our results demonstrate the reliability of CRP RDTs when compared to a reference standard. CRP RDTs without the need for a laboratory-based analyzer are promising tools for optimizing antibiotic use in low-resource settings.